Scleroderma Renal Crisis in a Case of Mixed Connective Tissue Disease Treated Successfully with Angiotensin-Converting Enzyme Inhibitors. (7th January 2021) - Madieh, Jomana; Khamayseh, Iman; Hrizat, Alaa; Hamadah, Abdurrahman; Gharaibeh, Kamel
Abstract : Mixed connective tissue disease (MCTD) is a rheumatic disease syndrome with overlapping features of scleroderma, systemic lupus erythematosus, and polymyositis. An extremely rare but serious complication that can occur in MCTD is scleroderma renal crisis (SRC). There have been different approaches to the treatment of SRC associated with MCTD. We present a case of MCTD with chronic features of Raynaud's phenomenon, dermatomyositis, and thrombocytopenia complicated with acute SRC which showed a great response to ACE inhibitors. Here, we advise the early and aggressive use of ACE inhibitors as soon as SRC is suspected.